Analysis of Merchandise Inventory Accounting System: Calculation Method - Selpi Mayarani; Safrizal Safrizal; Masril Masril (Jaanur Elbarik Indonesia, 2025)
This study aims to analyze the inventory accounting system of merchandise with a focus on the calculation method applied in the company. Inventory is an important component in financial statements that directly affects the cost of goods sold and net profit. Therefore, the selection of calculation methods has a significant impact on the presentation of financial information. This study uses a qualitative descriptive approach with data collection techniques through interviews, observations, and documentation studies in one of the trading companies. The results of the study indicate that the company uses a perpetual inventory recording system with the FIFO calculation method, which is in accordance with Financial Accounting Standards (SAK). This method provides a higher ending inventory value in rising price conditions, as well as increasing the company's net profit. Although the inventory accounting system applied is quite effective, there are several administrative constraints that still need to be fixed to improve the efficiency and accuracy of recording. Thus, the selection and application of the right calculation method is very important to produce reliable and relevant financial reports for decision making).